Library Book Search and Management System Using RFID Technology - Zulkiply, Muhammad Amir Zulhilmi; Mohd Noh, Faridah Hanim (Progress in Engineering Application and Technology, 2020)
This project is related to the common problem that occurred in almost all libraries in Malaysia. A library is a place where people can find any reading material to add knowledge. As a place for a learning center, a library plays a crucial role in academic fields, especially in universities, where many written materials are provided for students and staff. However, there are still obstacles faced by users, such as locating and borrowing books. In terms of locating books, many library-users cannot locate a specific book on the specific shelf in the library while some may miss-placed the books. In addition, the time needed to borrow or return books could be longer because they need to queue in line. This project aims to overcome the problem by developing a library book search and management system using RFID technology. This project consisted of two main parts, which are a radio-frequency identification (RFID) reader and its tag. There are also other components such as RTC 12C module and SD card module. These components have been programmed using Arduino that will be the brain of this project, and the RFID tag for each book consists of the book details. A reader will read the book tag within 3 cm from the reader display, regardless if the user wants to check in or check out the book. The reading data will be saved in the SD card slot, recording the time and date of the tag detected, and the process is successful. The prototype of the overall circuit is completely functional and able to give an output.